Analisis Perhitungan Pajak Penghasilan Pasal 21 atas Gaji Karyawan Berdasarkan Undang-Undang dan Peraturan Perpajakan Pada PT Petrona Mining Contractors - Angel Angreany Ivan Putri; Cornelius Rante Langi; Iskandar Iskandar (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
ANGEL ANGREANY IVAN PUTRI. Analisis Perhitungan Pajak Penghasilan Pasal 21 Atas Gaji Karyawan Berdasarkan Undang-Undang Dan Peraturan Perpajakan Pada PT Petrona Mining Contractors under the guidance Cornelius Rantelangi and  Iskandar.            The purpose of this paper is to analyze the calculation of Article 21 of income tax on employee salary of PT Petrona Mining Contractors based on laws and regulations.The Income tax deduction calculation data article 21 and was analyzed with “Undang-Undang No.36 tahun 2008” and “Peraturan Dirjen Pajak No. PER-16/PJ/2016” which provides an overview of the deduction, deposit and reporting of Income Tax article 21 relating to work, services and activities of private persons.As a result of analysis and consideration, the calculation of Article 21 of income tax of PT Petrona Mining Contractors by the company in January was Rp 4.818.497 and Rp 5.835.205 in February 2017. Beside in analyzed the calculation of Article 21 of income tax of PT Petrona Mining Contractors should be Rp 1.540.869 and Rp 2.103.762 in February 2017. So that the difference in January is Rp. 3,277,628 and in February Rp. 3,731,443 where the difference is the excess in paying taxes. This is due to differences in the calculation PTKP where the company calculates based on old regulations.